The Ancient Indian Alcoholic Drink Called Surā: Vedic Evidence - McHugh, James (JAOS, 2021)
A drink called surā is the alcoholic drink mentioned in our oldest Indian text, the Ṛg Veda, and people continued to make a drink called surā for millennia. This article uses the methodology of the comparative study of fermentation methods in order to make sense of the earliest descriptions of surā brewing processes. Surā was brewed in a semi-solid state, using malts for saccharification, perhaps also with a complex microbial ferment starter as one sees elsewhere in Asia today. Surā was not distilled. Understanding this has philological value: if surā was brewed with this process, we can better understand certain words associated with surā in Vedic texts, e.g., the drink called parisrut (“fluid[-grain mixture]”), certain material objects (the kārotara filter-structure), and certain processes (surā, etymologically as squeezing or pressing). Although brewing instructions are varied and may reflect several modes of brewing, and although the process in surviving descriptions may have been ritually inflected to highlight resemblances with soma pressing, I argue we can still get a sense of the basic method of brewing. These are some of the earliest detailed descriptions of brewing a grain drink that, considered in the long term, has similarities with both Mesopotamian brewing and East Asian methods.